Pengaruh Pemikiran Filsafat Barat Terhadap Pemikiran Moderen Islam - Muhammad Fikran Said; Abu Haif (CV. SINAR HOWUHOWU, 2026)
Philosophy is a discipline that emerged from human efforts to understand reality through rational and systematic inquiry. This study aims to examine the development of Western philosophical thought from ancient Greece to the modern and contemporary periods, as well as to analyze the distinctive characteristics of each philosophical era. The research employs a qualitative approach using library research by reviewing classical and modern philosophical literature. Data analysis is conducted through historical-philosophical and content analysis methods to explore paradigm shifts in philosophical thought within their social and intellectual contexts. The findings indicate that Western philosophy has undergone significant intellectual transformations, ranging from a cosmocentric orientation in ancient Greece, a theocentric approach in the medieval period, to rational and critical perspectives in the modern era. Each period has made substantial contributions to the development of epistemology and scientific thought. This study concludes that Western philosophy serves as a fundamental foundation for critical and rational thinking and remains highly relevant to contemporary scholarly discourse.